Assessment of maternal health status among pregnant women at Rangpur Medical College and Hospital, Bangladesh: A descriptive cross-sectional study - Md. Kamrul Hasan; Mst. Roksana Akter; Md. Sun Moon Islam (Kashmir Journal of Science, 2025)
This descriptive cross-sectional study aimed to evaluate the health status of pregnant women at Rangpur Medical College and Hospital (RMCH), Bangladesh. A total of 40 pregnant women were selected through non-probability sampling over a period of six months. Data were collected using semi-structured questionnaires and face-to-face interviews, focusing on antenatal care, obstetric, and sociodemographic characteristics. The average age of participants ranged between 24 and 28 years, with 97.5% being housewives. All participants were vaccinated against tetanus, and 78% had attended at least three antenatal check-ups. Statistical analysis revealed a significant association between age and antenatal visits (p<0.004) as well as gravida (p<0.002). Additionally, 2.5% of respondents reported co-morbidities such as hypertension, while 2.5% experienced pregnancy-related complications despite receiving antenatal care. The study underscores the need for heightened focus on high-risk pregnancies, particularly among older women and those with co-morbid conditions. Overall, the findings highlight the importance of antenatal care and immunization in mitigating maternal and fetal health risks. The study recommends enhancing maternal healthcare services to further reduce pregnancy-related complications.